A functional polymorphism of the stromelysin gene (MMP-3) influences susceptibility to primary sclerosing cholangitis. - Satsangi, J; Chapman, R; Haldar, N; Donaldson, P; Mitchell, S; Simmons, J; Norris, S; Marshall, SE; Bell, J; Jewell, D; Welsh, K (2001)
BACKGROUND AND AIMS: We have investigated the influence of a biallelic polymorphism of the promoter region of stromelysin (matrix metalloproteinase 3) on susceptibility to primary sclerosing cholangitis (PSC). The 5A allele is associated with increased transcription, compared with wild-type (6A). METHODS: An allelic association study was performed: in stage 1, 52 PSC patients (43 with inflammatory bowel disease [IBD]) and 99 healthy subjects (HS) were genotyped. In stage 2, 59 PSC patients (49 IBD), 84 patients with uncomplicated ulcerative colitis, and 72 HS were genotyped. RESULTS: In stage 1, 5A carriage rate (90.4% vs. 72.7%; P = 0.012) and 5A allelic frequency (65.4% vs. 48.5%; P = 0.005) were increased, and 6A homozygosity was reduced in PSC (9.6% vs. 27.3%; P = 0.012). In stage 2, 5A allelic carriage was increased in PSC (93.2% vs. 76.4% in HS; P = 0.0092) and 6A homozygosity was reduced (6.8% vs. 23.8% in HS; P = 0.0092). Portal hypertension was associated with 5A homozygosity in PSC (P = 0.035; odds ratio [OR], 3.88). In the combined data set, 5A allelic frequencies (63.5% vs. 49.4%; P = 0.001; OR, 1.78) and 5A carriage rates (91.9% vs. 74.2%; P = 0.0002; OR, 3.92) were increased, and 6A homozygosity was reduced in PSC (8.1% vs. 25.7%; P = 0.0002; OR, 0.25). Overall, portal hypertension was associated with 5A homozygosity (P = 0.0192; OR, 3.12). CONCLUSIONS: Stromelysin polymorphism may influence susceptibility and disease progression in PSC.